Implementasi Metode Role-Playing dalam Meningkatkan Pemahaman Konsep Bisnis di SMK Negeri 1 Pendalian IV Koto - Rukaiyah, Siti; A, Ma’shumi; Gusmita, Desi (EduSpirit : Jurnal Pendidikan Kolaboratif, 2025)
This study aims to analyze the implementation of the role-playing method in enhancing business concept comprehension at SMK Negeri 1 Pendalian IV Koto. The research employs Classroom Action Research (CAR) using the Kemmis and McTaggart model, which consists of planning, action, observation, and reflection in two cycles. The subjects are 11th-grade students who struggle to understand business concepts through conventional teaching methods. Data were collected through observations, interviews, business concept comprehension tests, and documentation. The findings indicate that applying the role-playing method significantly improves students’ understanding of business concepts. In the first cycle, comprehension increased by 20%, and in the second cycle, it improved by 40%. The role-playing method allows students to engage directly in business simulations, enabling them to grasp concepts more effectively through practical experience. This study concludes that the role-playing method is an effective strategy for enhancing business concept comprehension at the vocational high school level.